The hard edge of soft power: mega-events, geopolitics, and making nations great again - Wolfe, Sven Daniel (Mega event planning, 2025)
1. Introduction: Rationales and foundational concepts - Sven Daniel Wolfe -- 2. Geopolitics and international sporting events in the United Kingdom: Constitutional navel-gazing and the politics of event hosting - Stuart Whigham -- 3. When the stage came down: A short-term feel-good experience at South Africa’s World Cup - Rutendo Musikavanhu -- 4. Behind the golden glow: The soft power, Potemkinism, and protest of Australian mega-events - Max Holleran, Jennifer Minner, and Martin Abbott -- 5. Stepping out of the shadows: The role of pivotal individuals in Qatar’s aspirations to host mega-events - Tobias Zumbraegel and Sebastian Sons -- 6. From “being there is everything” to “go big or go home”? Comparing the opening ceremonies of the 2008 Summer Olympics and the 2022 Winter Olympics in Beijing - Julia Gurol -- 7. The authoritarian legacy: Mega-event security, the managerial-militarized model, and the rise of the far-right in Brazil - Bruno Cardoso and Dennis Pauschinger -- 8. The Eastern European mega-event decade: Sports, geopolitics, and war at the start of the 21st century - Vitaly Kazakov and Dmitrijs Andrejevs -- 9. The Salt Lake City 2002 Winter Olympics: Soft power, sportswashing, and the invasion of Iraq - Jules Boykoff and Reed McFeely -- 10. Conclusion: After the spotlight - Sven Daniel Wolfe.